IMPLEMENTING ISLAMIC VALUES FOR CHILDREN IN FAMILY - Abdul Hakim; Ahmad Fauzi; Benny Prasetiya (Al-ATHFAL: Jurnal Pendidikan Anak, 2020)
The role of religious education in the family environment is really needed, in shaping the personality of the children because they receive a very important education firstly from a family environment which can affect the development of a child. To get a good personality and avoid bad moral violations, therefore it is necessary to have religious guidance from an early age for the children in the family. The process of fostering religious values in shaping children's personalities can be started from birth to adulthood. Starting when they were born, they are introduced with a good sentence (kalimah thoyyibah), then after they grow and develop into children, the first thing that must be instilled is the religious values related to faith in Allah SWT and His Messenger, so that children believe in Allah SWT and can know Allah SWT confidently (ma'rifa tullah). Along with that, children are also guided about moral values in life, such as how to say good or polite words, dress well, get along or behave well, and so on. Good qualities are also instilled in children, such as the values of honesty, life justice, simplicity, patience, and others. Also, to make children have good moral values in the family environment, both the mother and the father must maintain their behavior or harmonize the relationship between the two and must be the role models for their children